Selected Areas in Cryptography - SAC 2013: 20th International Conference, Burnaby, BC, Canada, August 14-16, 2013, Revised Selected Papers - SAC; Lange, Tanja; Lauter, Kristin; Lisonĕk, Petr (Lecture Notes in Computer Science, 2014)
This book constitutes the proceedings of the 20th International Conference on Selected Areas in Cryptography, SAC 2013, held in Burnaby, Canada, in August 2013. The 26 papers presented in this volume were carefully reviewed and selected from 98 submissions. They are organized in topical sections named: lattices; discrete logarithms; stream ciphers and authenticated encryption; post-quantum (hash-based and system solving); white box crypto; block ciphers; elliptic curves, pairings and RSA; hash functions and MACs; and side-channel attacks. The book also contains 3 full-length invited talks.